Zastosowanie metod taksonomicznych do badania poziomu życia w powiatach województwa małopolskiego - Badach, Elżbieta; Zioło, Monika (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2012)
The aim of the paper is to classify districts of Małopolskie Voivodship with respect to the quality of live of the inhabitants. In order to do this the synthetic variable was constructed with the usage of Hellwig method; the diagnostic variables constituting the basis for this construction were such as the average income in given district, the level of unemployment, average area of flat and number of beds in hospitals per 10 thousand inhabitants. The analysis was based on the GUS data from 2009. As the result of the classification four groups of districts similar with respect to the quality of life were obtained.